2009
DOI: 10.1111/j.1743-6109.2008.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Regulation of Ejaculation

Abstract: Introduction Delineation of the underlying neurophysiological mechanisms of ejaculatory behavior is crucial for the treatment of male sexual dysfunction, including premature ejaculation. Recent studies provide compelling evidence that a population of lumbar spinothalamic (LSt) cells may play a role in the regulation of the ejaculatory response. Subsequent to ejaculation, LSt cells exhibit markers of activation that are not only highly correlated with ejaculatory behavior, but are also absent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
(37 reference statements)
1
6
0
2
Order By: Relevance
“…Stimulation of serotonin receptors of the 5‐HT 2 subtypes is often followed by inhibition of seminal emission and ejaculation in many animal models (mice, rats, etc.). Similar results can be obtained by stimulating central and spinal presynaptic 5‐HT 1A autoreceptors which inhibit serotonin release [52–55]. The most studied CNS sites where stimulation of 5‐hydroxytryptamine (5‐HT) receptors causes delay of seminal emission and ejaculation are the medial preoptic area and the spinal cord.…”
Section: Central Nervous System (Cns) Targets For Male Sexual Dysfuncsupporting
confidence: 61%
“…Stimulation of serotonin receptors of the 5‐HT 2 subtypes is often followed by inhibition of seminal emission and ejaculation in many animal models (mice, rats, etc.). Similar results can be obtained by stimulating central and spinal presynaptic 5‐HT 1A autoreceptors which inhibit serotonin release [52–55]. The most studied CNS sites where stimulation of 5‐hydroxytryptamine (5‐HT) receptors causes delay of seminal emission and ejaculation are the medial preoptic area and the spinal cord.…”
Section: Central Nervous System (Cns) Targets For Male Sexual Dysfuncsupporting
confidence: 61%
“…Moreover, this neural activation of LSt cells is essential for ejaculatory reflexes induced by DPN stimulation as pharmacological blockade of ERK and NMDA receptor activation prevented BCM bursting characteristic of ejaculation following DPN stimulation [28,29]. Finally, LSt cells have direct axonal intraspinal connections with autonomic sympathetic (IML and CAN) and parasympathetic (SPN) neurons within the spinal cord [23,27,30–33] and project to pudendal motorneurons [34]. Thus, LSt cells have been demonstrated to form an essential component of the spinal ejaculation generator.…”
Section: Introductionmentioning
confidence: 99%
“…Ejaculation is a reflex mediated by a spinal ejaculation generator that consists of a population of interneurons at lumbar levels 3‐4 (lumbar spinothalamic cells; LSt) and their projections to autonomic and motor areas within the lumbosacral spinal cord [1–5]. Previous studies from our laboratory and others have indicated that LSt cells are essential for ejaculation as LSt cell lesions ablate ejaculatory behavior in intact mating animals [4].…”
Section: Introductionmentioning
confidence: 99%